Hydropneumatic Suspension Systems - Bauer, Wolfgang (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Hydropneumatic suspensions systems combine the excellent properties of gas springs with the favourable damping properties of hydraulic fluids. The advantages of these systems are particularly appropriate for automotive applications, such as passenger cars, trucks and agricultural equipment. In this book, Dr. Bauer provides an extensive overview of hydropneumatic suspension systems. Starting with a comparison of different types of suspension systems, the author subsequently describes the theoretical background associated with spring and damping characteristics of hydropneumatic systems and furthermore explains the design of the most important system components. Additionally he gives an overview of level control systems and various special functions. Finally the technology is illustrated by design examples and the outlook for future hydropneumatic suspensions is discussed.